The Development of Personal Data Protection Law in Indonesia: Challenges and Prospects for the Implementation of Law No. 27 of 2022 - Budiman, Risky (Inovasi Pratama Internasional. Ltd, 2023)
Indonesia’s enactment of Law No. 27 of 2022 on Personal Data Protection (PDP Law) marks a significant milestone in the country’s legal landscape, aligning national regulations with global standards such as the European Union’s General Data Protection Regulation (GDPR). This qualitative research examines the evolution of personal data protection law in Indonesia, the main challenges encountered during the initial phase of implementation, and the prospects for effective enforcement. The study employs a normative legal approach, analyzing statutory provisions, secondary legal materials, and recent case studies. Findings indicate that while the PDP Law provides a comprehensive legal framework and establishes clear rights and obligations for data controllers and subjects, substantial challenges remain, including institutional readiness, public awareness, and enforcement capabilities. The paper concludes by discussing the prospects for robust data protection in Indonesia and offers recommendations for strengthening the implementation of the PDP Law.